Ultrathin, Washable, and Large‐Area Graphene Papers for Personal Thermal Management. Issue 44 (29th September 2017) - Guo, Yang; Dun, Chaochao; Xu, Junwei; Mu, Jiuke; Li, Peiyun; Gu, Liwen; Hou, Chengyi; Hewitt, Corey A.; Zhang, Qinghong; Li, Yaogang; Carroll, David L.; Wang, Hongzhi
Abstract: Freestanding, flexible/foldable, and wearable bifuctional ultrathin graphene paper for heating and cooling is fabricated as an active material in personal thermal management (PTM). The promising electrical conductivity grants the superior Joule heating for extra warmth of 42 °C using a low supply voltage around 3.2 V. Besides, based on its high out‐of‐plane thermal conductivity, the graphene paper provides passive cooling via thermal transmission from the human body to the environment within 7 s. The cooling effect of graphene paper is superior compared with that of the normal cotton fiber, and this advantage will become more prominent with the increased thickness difference. The present bifunctional graphene paper possesses high durability against bending cycles over 500 times and wash time over 1500 min, suggesting its great potential in wearable PTM. Abstract : A wearable personal thermal management device based on graphene paper is demonstrated with multiple construction designs. For heating, the temperature can be raised from 18 to 38 °C with a typical supply voltage of 3.2 V within 8 s. For cooling, the response time is greatly shortened from 150 to 7 s compared with normal cotton fabric.